Development of the method to operatively control quality of iron ore raw materials at open and underground extraction - Azaryan, Albert; Gritsenko, Andrey; Trachuk, Annait; Shvets, Dmitriy (Eastern-European Journal of Enterprise Technologies, 2018)
The main task of the mining industry is to improve the efficiency of extraction and processing of iron ore. One of the main factors contributing to solving the task is determining the content of iron in the ore body at the initial stage of production chain. Traditional methods of chemical analysis that are widely used at present to achieve this goal do not possess a sufficient degree of responsiveness and require about two hours to obtain the results. That typically does not make it possible to properly adjust the parameters of the technological process of ore processing, but only provides for the opportunity to ascertain the status of the production process at the time of sampling. Existing methods of accomplishing this task, which possess a sufficient degree of efficiency, are based on the use of direct methods. These include the nuclear-physical (interaction between gamma-radiation and mountain mass), magnetometric (changing the relative magnetic permeability when interacting with magnetic iron), ultrasound (a change in the ultrasonic wave propagation in the examined material) methods. In order to improve the accuracy of determining the percentage of a mineral component in the examined mountain mass, in this work we have improved the nuclear-physical method for determining the content of total iron in iron ore lumps. The improvement of the method makes it possible to enhance the accuracy of control over a mineral component in the studied material by 1.5 % by registering not only the gamma quanta reflected from the surface, but the absorbed particles as well. We have experimentally established the sensitivity level (K=1.32‒1.38), which characterizes a change in the intensity of the registered radiation due to a change in the content of iron in the irradiated material. We have also established the level of a statistical error (<0.65 %) in order to ensure the permissible measurement accuracy. Based on a given method, we have proposed an information-measuring system for monitoring, analysis, and forecasting the qualitative characteristics of ore under conditions of an enrichment plant. The application of this system makes it possible for technological personnel to promptly intervene in the production process and to adjust the qualitative-quantitative parameters of ore